PERAN PUPUK CAIR ORGANIK URIN SAPI UNTUK PERTUMBUHAN BIBIT ADENIUM (Adenium obesum) PADA BEBERAPA MACAM KOMBINASI MEDIA TUMBUH - Mohamad Ihsan Mohamad Ihsan (AGRONOMIKA, 2016)
The objective of this research was to know the influence of foliar organic fertilizer and three kinds of cattle manure organic fertilizer on growth of adenium seedling. This pot experiment was conducted in the  glass house which arranged as factorial Completely Randomized Design with two factors as treatment that were: concentration of cow urine as foliar fertilizer i.e. : 0 cc/ lt of water, 2,5 cc/lt of water, 5 cc/ lt of water and 7,5 cc/ lt of water. The second factor was application of organic fertilizer that were three kinds of cattle manure that were: cow, goat and chicken.  The adenium seedling planted and there were several parameters of plant growth were observed. Result of research showed that there significant relation between the kind of cattle manure organic fertilizer application toward all parameters of plant growth observed. Can be concluded that there was not significant influence of foliar fertilization on adenium seedling growth. The best cattle organic fertilizer was chicken manure which combine with application of cow urine 5 cc/ lt  of  water